2015
DOI: 10.1097/md.0000000000000767
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles and Clinical Significance of MicroRNAs in Papillary Renal Cell Carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…miRNAs show aberrant expression profiles in various cancers, and dysregulation of miRNAs may alter the neoplastic progression and prognosis of human malignancies. 19 , 20 As the previous studies described, miRNA expression data were open access in the TCGA data portal, and analyzing the TCGA data has already become an important approach to investigate the association between miRNA expression patterns and pathologic characteristics and survival in various cancer types, including lung cancer, 12 hepatocellular carcinoma, 21 renal cell carcinoma, 22 and bladder cancer. 23 For LUAD patients, Li et al 12 identified an eight-miRNA signature for predicting the OS by mining the TCGA data before.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs show aberrant expression profiles in various cancers, and dysregulation of miRNAs may alter the neoplastic progression and prognosis of human malignancies. 19 , 20 As the previous studies described, miRNA expression data were open access in the TCGA data portal, and analyzing the TCGA data has already become an important approach to investigate the association between miRNA expression patterns and pathologic characteristics and survival in various cancer types, including lung cancer, 12 hepatocellular carcinoma, 21 renal cell carcinoma, 22 and bladder cancer. 23 For LUAD patients, Li et al 12 identified an eight-miRNA signature for predicting the OS by mining the TCGA data before.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cases with OS <1 month were removed, which may affect the results of survival analysis. Ge et al 22 divided cases into two groups (follow-up time >30 days and <30 days) in the previous study and found that the survival-related miRNAs differed according to whether these cases with OS <1 month were included. Thus, given the differences in the approaches for the selection of cases and miRNAs, the authors identified differentially expressed miRNAs between LUAD and adjacent normal tissues with the TCGA dataset following the strict exclusion criteria and explored the cancer-specific miRNAs for predicting the development and survival in patients with LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-3074 has been associated with papillary renal cell carcinoma [108], but no publication is available about its role in BC.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNA target prediction was conducted using three computational algorithms including TargetScan (version 7.1; http://www.targetscan.org ) 33 , miRDB ( http://www.mirdb.org/ ) 34 , and the Good mirSVR score collection within miRanda ( http://www.microrna.org ) 35 . The genes predicted by at least two independent tools were uploaded to the Database for Annotation, Visualization and Integrated Discovery (DAVID) program (version 6.8; https://david.ncifcrf.gov/ ) 36 , 37 for further annotation analyses including Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, as we previously reported 21 .…”
Section: Methodsmentioning
confidence: 99%